Antibody fragments as nanoparticle targeting ligands: a step in the right direction. Issue 1 (16th September 2016) - Richards, Daniel A.; Maruani, Antoine; Chudasama, Vijay
Abstract : Recent advances in nanomedicine have shown that dramatic improvements in nanoparticle therapeutics and diagnostics can be achieved through the use of disease specific targeting ligands. Abstract : Recent advances in nanomedicine have shown that dramatic improvements in nanoparticle therapeutics and diagnostics can be achieved through the use of disease specific targeting ligands. Although immunoglobulins have successfully been employed for the generation of actively targeted nanoparticles, their use is often hampered by the suboptimal characteristics of the resulting complexes. Emerging data suggest that a switch in focus from full antibodies to antibody derived fragments could help to alleviate these problems and expand the potential of antibody–nanoparticle conjugates as biomedical tools. This review aims to highlight how antibody derived fragments have been utilised to overcome both fundamental and practical issues encountered during the design and application of antibody–targeted nanoparticles.